Low-Molecular-Weight Heparin in Cancer Patients: Overview and Indications - Voigtlaender, Minna; Langer, Florian (Hämostaseologie, 2019)
Although venous thromboembolism (VTE) is a well-known cause of death in patients with cancer, both its treatment and prevention remain a challenge in daily practice. Direct oral anticoagulants have emerged as safe and efficacious alternatives to vitamin K antagonists in the general population, and recent clinical trials also support their use in select patients with cancer-associated VTE. Despite this, low-molecular-weight heparins (LMWHs), a comparatively ancient class of antithrombotic drugs, remain the anticoagulants of choice in many indications relevant to modern haematology and oncology. In addition to the treatment of established VTE, these indications include VTE prophylaxis in surgical or acutely ill, hospitalized medical cancer patients as well as the prevention of VTE in high-risk patients undergoing ambulatory chemotherapy. In a constantly changing landscape of approved anticancer agents, this review article summarizes pivotal clinical trial data and guideline recommendations regarding the use of LMWH in haematological and oncological patients, who constitute a highly vulnerable patient population due to their increased risk for both bleeding and VTE recurrence.
Keywords: low-molecular-weight heparin; venous thromboembolism; cancer